A positive theory of the earnings relationship of unemployment benefits - Laszlo Goerke; Markus Pannenberg; Heinrich W. Ursprung (Institute for the Study of Labor (IZA), 2007)
Evidently, the benefit-structure of the unemployment insurance has a significant influence on profits and trade union utility. We show for a wage bargaining model that a stronger earnings relationship of unemployment benefits may reduce wages and increase employment. This raises the question as to how the benefit structure is determined in the political process. To answer this question, we consider a government that chooses the earnings relationship with a view to maximising its political support. Our model predicts a strong earnings relationship under right-wing governments and a weak one when the unions' influence is pronounced. Deepening international economic integration has ambiguous effects. Using panel data for 19 OECD countries from 1961 to 2003 we find support for the hypothesized domestic influences and show that the earnings relationship varies negatively with openness.
Keywords: 330; Arbeitslosenversicherung; Lohnersatzleistungen; Einkommen; Lohnverhandlungstheorie; Public Choice; Theorie; OECD-Staaten